Satisfaction Level Among Obstetric Clients to the Delivery of Basic Emergency Obstetric and Newborn Care Services - Edmelyn B. Cacayan; Maria Tessa M. Alingog; Rianne Maie Castillo Mangaoil (Humanistic Network for Science and Technology (HNST), 2020)
The Department of Health launched a special program called Basic Emergency Obstetric and Newborn Care (BEmONC) that aims to reduce at maternmal and fetal mortality. The purpose of this study is to determine the satisfaction level among obstetric clients on the delivery of BEmONC services at the Rural Health Unit-Angadanan. A descriptive-inferential method was used. A survey questionnaire was administered to the 26 respondents, who consulted and delivered at the Rural Health Unit-Angadanan from the month of December 2014. The results revealed that the respondents were immensely satisfied with the services such as assessing and monitoring vital signs, essential newborn care and counseling on exclusive breast feeding, proper nutrition and essential neonatal care. However, respondents were not so satisfied with the times allotted in availing maternal services and to the administration of steroids for premature labor. Those respondents who are older and those with lower income tend to have higher satisfaction rate. Community-based practice should focus on providing the fastest possible time in availing the needed maternal care and explaining emergency procedure to the clients to increase their awareness. Keywords: obstetric; newborn